Buddha Bihar (Kiyang) based traditional model for tree diversity conservation in Rangamati Hills, Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2018)
This paper describes Buddha Bihar (Kiyang) based biodiversity conservation of Nirbanpur in Rangamati Hill District of Bangladesh. Rangamati is the native of the tribal people specially the Chakma and they are the followers of the Bhudda religion. This Bihar comprised of 300 acres of hilly land and maintaining natural patches having 76 indigenous tree species. Most of the tribal people of this district belong to Buddha religion and they strongly believe in the biodiversity conservation around their religious institute and most of them are situated at hill top of the deep forest areas. This institution is maintained by the religious leaders locally called as Bantheya and the local community people have great respect for them. Most of the Bantheyas are conserving biodiversity in traditional way which is unique model for local level biodiversity conservation and local people also consider these plants as taboos or secrete trees. Bihar management committee maintains some traditional rules in plant conservation, but now they are leaned towards commercial plantation. BFRI scientists try to motivate them towards plantation indigenous species by awareness meeting. The seedlings of 32 indigenous tree species were planted in the Bihar area which has enhanced the diversity of flora and fauna. A biodiversity conservation model having four pillars has been developed on consultation with the community and religion leaders. The theme of pillars are land tenure, traditional knowledge, awareness and support. Bihar based biodiversity conservation effort has created a new avenue for wildlife and bird conservation. A list of existing plants species around Nirbanpur Bihararea has been given.J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(1): 27-34